You are on page 1of 16

Exercise 2.

6 (Solutions)
MathCity.org Calculus and Analytic Geometry, MATHEMATICS 12
Merging man and maths Available online @ http://www.mathcity.org, Version: 3.0

2.10 Derivative of General Exponential Function (Page 80)


A function define by
f ( x) = a x where a > 0, a ≠1
is called general exponential function.
Suppose y = ax
⇒ y + δ y = a x+δ x ⇒ δ y = a x+δ x − y
⇒ δ y = a x+δ x − a x Since y = a x
⇒ δ y = a x (aδ x −1)
Dividing by δ x
δ y a x (aδ x −1)
=
δx δx
Taking limit as δ x → 0
δy a x (aδ x −1)
lim
δ x →0 δ x
= lim
δ x →0 δx
dy  δ x −1 
x a dy  a δ x −1 
⇒ = lim a   ⇒
x
= a δlim  
dx δ x→0  δ x  dx x →0  δ x 
 
d x a x −1
⇒ (a ) = a x .ln a Since lim = ln a
dx x →0 x

Derivative of Natural Exponential Function


The exponential function f ( x) = e x , where e = 2.71828... , is called Natural
Exponential Function.
Suppose y = ex
Do yourself … Just Change a by e in above article. You’ll get
d x
e = ex
dx

2.11 Derivative of General Logarithmic Function (page 81)


If a > 0, a ≠ 1 and x = a y , then the function defined by y = log a x ( x > 0) is
called General Logarithmic Function.
Suppose y = log a x
⇒ y + δ y = log a ( x + δ x) ⇒ δ y = log a ( x + δ x) − y
⇒ δ y = log a ( x + δ x) − log a x
 x +δ x  m
= log a   Since log a m − log a n = log a
 x  n
Dividing both sides by δ x
δy 1  x +δ x 
= log a  
δx δx  x 
FSc-II / Ex- 2.6 - 2 MathCity.org

Taking limit as δ x → 0
δy 1  x +δ x 
lim = lim
δ x →0 δ x δ x →0 δ x
log a  
 x 
dy 1  δx 
⇒ = δlim log 1 +
dx x →0 δ x a
 x 
x 1  δx 
= δlim ⋅ log 1 + ÷ing and ×ing by x
x →0 x δ x a
 x 
dy 1 x  δx 
⇒ = δlim log 1 +
dx x x→0 δ x a
 x 
x
dy 1  δ x δ x
⇒ = δlim log 1 + Since m log a x = log a x m
dx x x→0 a
 x 
 x

dy 1   δx  xδ
⇒ = log a δlim 1+
dx x  x→0  x  
 
1
dy 1
⇒ = log a e Since lim (1 + x ) x = e
dx x x →0
d 1 1 1
⇒ ( log a x ) = Since log a b =
dx x log e a logb a
d 1
⇒ ( log a x ) = Since log e a = ln a
dx x ln a

Derivative of Natural Logarithmic Function


The logarithmic function f ( x) = log e x where e = 2.71828... is called Natural
Logarithmic Function. And we write ln x instead of log e x for our ease.
Suppose y = ln x
⇒ y + δ y = ln ( x + δ x) ⇒ δ y = ln ( x + δ x) − y
⇒ δ y = ln ( x + δ x) − ln x
 x +δ x  m
⇒ δ y = ln   Since ⇒ ln m − ln n = ln
 x  n
 δx 
= ln 1 +
 x 
Dividing both sides by δ x
δy 1  δx 
= = ln 1 +
δx δx  x 
Taking limit as δ x → 0
δy 1  δx 
lim = lim ln 1 +
δ x →0 δ x δ x →0 δ x
 x 

http://www.mathcity.org
MathCity.org FSc-II / Ex- 2.6 - 3

dy x 1  δx 
⇒ = δlim ⋅ ln 1 + ÷ing and ×ing by x
dx x →0 x δ x
 x 
dy 1 x  δx 
⇒ = δlim ln 1 +
dx x x→0 δ x  x 
x
dy 1  δ x δ x
⇒ = δlim ln 1+ Since m ln x = ln x m
dx x x→0  x 
 x

dy 1   δx  x
δ
⇒ = ln lim 1 +
dx x δ x→0  x  
 
1
dy 1
⇒ = ln e Since lim (1+ x ) x = e
dx x x →0
d 1
⇒ ( ln x ) = ⋅1 Since ln e = log e e =1
dx x
d 1
⇒ ( ln x ) =
dx x

Exercise 2.6 (Questions)


Question # 1
Find f ′( x) if
1
(i) f ( x ) = e x −1
(ii) f ( x ) = x e , ( x ≠ 0 )
3 x
(iii) f ( x) = e x (1 + ln x )
ex eax − e− ax
(iv) f ( x) = − x
e +1
(v) f ( x) = ln e + e ( x −x
) (vi) f ( x) = ax
e + e− ax
(vii) f ( x) = (
ln e2 x + e− 2 x ) (viii) f ( x) = ln (e 2x
+ e− 2 x )
Solution
(i) f ( x) = e x −1
Diff. w.r.t x
d d x −1
f ( x) = e
dx dx
d
⇒ f ′( x) = e x −1

dx
x −1 ( )
x −1  1 
1
− e x −1
= e  x 2 − 0 = Ans.
2  2 x

1
3 x
(ii) f ( x) = x e
Diff. w.r.t x

http://www.mathcity.org
FSc-II / Ex- 2.6 - 4 MathCity.org
1
d d 3 x
f ( x) = xe
dx dx
1 1
3 d d 3
⇒ f ′( x) = x e +ex
x
x
dx dx
1 1
3 x d 1
= xe   + e 3x
dx  x 
x 2
( )
1 1
3 x 1  x d  1  d −1 1
= x e  − 2  + e 3x 2
 x 
( ) ∵
dx  x  dx
−2
  = x = −x = − 2
x
1 1 1
= − xe + 3 x e
x 2 x
= xe ( 3 x − 1)
x
Ans.

(iii) f ( x) = e x (1 + ln x )
Diff. w.r.t x
d d x
f ( x) = e (1 + ln x )
dx dx
d d
⇒ f ′( x) = e x (1 + ln x ) + (1 + ln x ) e x
dx dx
 1
= e x  0 +  + (1 + ln x ) e x
 x
1   1 + x (1 + ln x ) 
⇒ f ′( x) = e x  + 1 + ln x  or f ′( x) = e x  
x   x 

ex
(iv) f ( x) =
e− x + 1
Diff. w.r.t x
d d  ex 
f ( x) =  
dx dx  e − x + 1 
d x d −x
(
e− x + 1
dx
e − ex) dx
e +1 ( )
⇒ f ′( x) = 2
e− x + 1 ( )
=
(e −x
) (
+ 1 e x − e x e− x (−1) + 0 ) =
(
e x e − x + 1 + e− x )
2 2
(e −x
+1 ) (e −x
)
+1
e ( 2e + 1)
x −x

⇒ f ′( x) = 2
Ans.
( e + 1)
−x

http://www.mathcity.org
MathCity.org FSc-II / Ex- 2.6 - 5

(v) (
f ( x) = ln e x + e − x )
Diff. w.r.t x
d d
dx
f ( x) =
dx
ln e x + e− x ( )
1 d x
⇒ f ′( x) = e + e− x ( )
x −x
e + e dx ( )
1
= (e x
+ e − x (−1) )
( e + e− x
x
)
e x − e− x e x − e− x
⇒ f ′( x) = x or f ′( x) = tanh x ∵ tanh x = x − x
e + e− x e +e
eax − e− ax
(vi) f ( x) =
eax + e− ax
Diff. w.r.t x
d d  e ax − e − ax 
f ( x) =  
dx dx  e ax + e − ax 

( eax + e− ax ) dxd ( eax − e−ax ) − ( eax − e− ax ) dxd ( eax + e−ax )


= 2
( eax + e− ax )
=
(e ax
+ e− ax )( eax (a ) − e − ax (− a ) ) − ( eax − e− ax )( eax (a ) + e − ax (− a ) )
− ax 2
(e + e ) ax

a ( e + e )( e + e ) − a ( e − e )( e
ax − ax ax − ax ax − ax ax
− e − ax )
=
− ax 2
(e + e ) ax

a ( e + e ) − ( e − e ) 
ax − ax 2 ax − ax 2
 
= 
− ax 2
(e + e ) ax

a (e2 ax + e−2 ax + 2eax e− ax ) − (e2 ax + e−2 ax − 2eax e− ax ) 


= 2
(e ax
+ e− ax )
a e2 ax + e−2 ax + 2 − e 2 ax − e−2 ax + 2 
= ∵ e ax e − ax = e0 = 1
− ax 2
(e ax
+e )
4a
⇒ f ′( x) = 2
Ans.
( eax + e− ax )

http://www.mathcity.org
FSc-II / Ex- 2.6 - 6 MathCity.org

(vii) f ( x) = (
ln e2 x + e− 2 x )
1
d d  2

dx
f ( x) =
dx 
ln e 2x
+ e −2x
( )
1 −1 d
⇒ f ( x) = ln e + e
′ 2x
( −2x
 2
)
ln e2 x + e− 2 x ( )
2  dx
1 1 d 2x
= ⋅ e + e− 2 x ( )
1
2 ln e 2 x + e − 2 x  2 e + e
(
2x − 2x
) dx ( )
1 1
= ⋅ 2x e 2 x (2) + e− 2 x (−2) ( )
) ( )
−2x
2 ln e + e2x
( −2x e +e

=
1

( 2 e2 x − e− 2 x ) =
(e 2x
− e− 2 x ) Ans.
) (e + e− 2 x )
2x
(
2 ln e 2 x + e− 2 x ( e2 x + e− 2 x ) (
ln e 2 x + e− 2 x )
(viii) f ( x) = ln (e 2x
+ e− 2 x )
1
1
(
= ln e + e 2x
)
− 2x 2
⇒ f ( x) =
2
(
ln e 2 x + e − 2 x ) ∵ ln x m = m ln x
Now diff. w.r.t x
d 1 d
dx
f ( x) =
2 dx
ln e2 x + e− 2 x ( )
Now do yourself
Question # 2
dy
Find if
dx
x
(i) y = x 2 ln x (ii) y = x ln x (iii) y =
ln x
1 x2 − 1
(iv) y = x ln 2

x
(v) y = ln 2
x +1
(vi) y = ln x + x 2 + 1 ( )
(
(vii) y = ln 9 − x 2 ) (viii) y = e −2 x sin 2 x (ix) y = e− x x3 + 2 x 2 + 1 ( )
x
(x) y = xesin x (xi) y = 5e3 x −4 (xii) y = ( x + 1)
ln x x 2 − 1 ( x + 1)
(xiii) y = ( ln x ) (xiv) y = 32
(x 3
+1 )
Solution
(i) y = x 2 ln x

http://www.mathcity.org
MathCity.org FSc-II / Ex- 2.6 - 7

1 1 2
⇒ y = x 2 ln ( x ) 2 ⇒ y = x ln x ∵ ln x m = m ln x
2
Now diff. w.r.t x
dy 1 d 2
= x ln x
dx 2 dx
1 d d 
=  x 2 ln x + ln x x 2 
2  dx dx 
1 1  1 1
=  x 2 ⋅ + ln x(2 x)  = x + x ln x or x + 2 x ln x Ans.
2 x  2 2

(ii) y = x ln x
Diff. w.r.t x
dy d 1
= x ( ln x ) 2
dx dx
d 1 1 d
= x ( ln x ) 2 + ( ln x ) 2 ( x)
dx dx
1 −1 d 1 x 1 1
= x ⋅ ( ln x ) 2 ( ln x ) + ( ln x ) 2 (1) = 1   + ( ln x ) 2
2 dx 2 ( ln x ) 2  x 
1 1 + 2ln x
= + ln x = Answer
2 ln x 2 ln x

x
(iii) y =
ln x
dy d  x 
⇒ =  
dx dx  ln x 
dx d 1
ln x − x ln x ln x (1) − x ⋅
= dx dx = x = ln x − 1 Answer
2 2 2
( ln x ) ( ln x ) ( ln x )
1
(iv) y = x 2 ln
x
⇒ y = x ln x −1
2
⇒ y = − x 2 ln x
Now do yourself.

x2 − 1
(v) y = ln
x2 + 1

http://www.mathcity.org
FSc-II / Ex- 2.6 - 8 MathCity.org
1
 x2 − 1  2 1  x2 − 1 
⇒ y = ln  2  ⇒ y = ln  2 
 x + 1  2  x +1
Now diff. w.r.t x
dy 1 d  x2 − 1 
= ln  
dx 2 dx  x 2 + 1 
1 1 d  x2 − 1 
= ⋅ 2 ⋅  
2  x − 1  dx  x 2 + 1 
 2 
 x +1
 2 d 2 d 2 
x +1 2 ( ) ( 2
 x + 1 dx x − 1 − x − 1 dx x + 1  ) ( ) ( )
= ⋅ 
(
2 x2 − 1 )  x2 + 1
2
( )
 
1  x2 + 1 ( 2 x ) − x2 − 1 ( 2x ) 
( ) ( )
= ⋅ 
(
2 x −1 2
)  x 2
+ 1 ( )
 
1  2x x2 + 1 − x2 + 1 
( 1  x ( 2)
)  2x
= ⋅ = ⋅ 2 = Ans.
(
2 x −1 2
)  x 2
+ 1(  ) x 2
− 1  x +1 ( ) ( )  ( 4
x −1 )
   

(vi) (
y = ln x + x 2 + 1 )
Diff. w.r.t x
dy d
dx
=
dx
(
ln x + x 2 + 1 )
1 d 1  1 2 −1 d 
=
x + x 2 + 1 dx
x + x2 + 1 = (  1
x + x2 + 1  2
+ )
x + 1 2
dx
x2 + 1 

( ) ( )
 
1 1 + 1  = 1  x 
= ⋅ ( 2 x )  1 + 
x + x 2 + 1  2 x 2 + 1 2 
1
( x + x2 + 1 
) x2 + 1 
 
 x2 + 1 + x 
1 1
=   = Answer
2 
x + x +1  x + 1 
2
x +12

(vii) y = ln 9 − x 2 ( )
Diff. w.r.t x
dy d
dx
=
dx
ln 9 − x 2 ( )

http://www.mathcity.org
MathCity.org FSc-II / Ex- 2.6 - 9

1 d 1
= 2
9 − x dx
⋅ 9 − x2( ) =
9 − x2
⋅( − 2 x )
dy −2 x
⇒ =
dx 9 − x2

(viii) y = e −2 x sin 2 x
dy d −2 x
⇒ = e sin 2 x
dx dx
d d
= e −2 x sin 2 x + sin 2 x e−2 x
dx dx
= e cos 2 x (2) + sin 2 x e −2 x (−2)
−2 x
= 2e−2 x ( cos 2 x − sin 2 x ) Answer

(ix) (
y = e− x x3 + 2 x 2 + 1 )
Diff. w.r.t x
dy d −x 3
dx
=
dx
(
e x + 2 x2 + 1 )
d 3 d −x
= e− x
dx
( ) (
x + 2 x 2 + 1 + x3 + 2 x 2 + 1
dx
e )
( ) (
= e − x 3 x 2 + 4 x + 0 + x3 + 2 x 2 + 1 ⋅ e− x (−1) )
= e− x ( 3x + 4 x ) − ( x + 2 x
2 3 2
)
+ 1 ⋅ e− x ( )
= e − x 3x 2 + 4 x − x3 − 2 x 2 − 1
= e− x ( − x + x + 4 x − 1)
3 2
Answer

(x) y = xesin x
Diff w.r.t x
dy d sin x
= xe
dx dx
d d
= x esin x + esin x x
dx dx
d
= x ⋅ esin x sin x + esin x (1) = x ⋅ esin x cos x + esin x
dx
= e ( x cos x + 1)
sin x
Answer

(xi) Do yourself

x
(xii) y = ( x + 1)
Taking log on both sides

http://www.mathcity.org
FSc-II / Ex- 2.6 - 10 MathCity.org
x
ln y = ln ( x + 1) ⇒ ln y = x ln ( x + 1)
Diff w.r.t x
d d
ln y = x ln ( x + 1)
dx dx
1 dy d dx
⇒ = x ln ( x + 1) + ln ( x + 1)
y dx dx dx
1 d
= x⋅ ( x + 1) + ln ( x + 1) (1)
x + 1 dx
 x
(1) + ln ( x + 1) 
dy
⇒ = y
dx  x +1 
x x 
= ( x + 1)  + ln ( x + 1)  Answer
 x +1 

ln x
(xiii) y = ( ln x )
Taking log on both sides
ln x
ln y = ln ( ln x ) ⇒ ln y = (ln x) ⋅ ln ( ln x )
Diff w.r.t x
d d
ln y = (ln x) ⋅ ln ( ln x )
dx dx
1 dy d d
⇒ = (ln x) ln ( ln x ) + ln ( ln x ) (ln x)
y dx dx dx
1 d 1
= (ln x) ⋅ ( ln x ) + ln ( ln x ) ⋅
ln x dx x
1 ln ( ln x ) 1 + ln ( ln x )
= + =
x x x
dy  1 + ln ( ln x )  dy ln x  1 + ln ( ln x ) 
⇒ = y  ⇒ = ( ln x )  
dx  x  dx  x 

(xiv) y =
x 2 − 1 ( x + 1)
⇒ y =
( ( x + 1)( x − 1) ) 2 ( x + 1)
32 3
( x3 + 1 ) ( x + 1) x 2 − x + 1  2
 (  )
1 1 3 1
( x + 1) 2 ( x − 1) 2 ( x + 1) ( x + 1) 2 ( x − 1) 2
⇒ y = 3 3 ⇒ y = 3 3
( x + 1) 2
(x 2
− x +1) 2
( x + 1) 2
(x 2
− x +1 ) 2

http://www.mathcity.org
MathCity.org FSc-II / Ex- 2.6 - 11
1
( x − 1) 2
⇒ y = 3
(x 2
− x +1 ) 2

Taking log on both sides


1
( x − 1) 2
ln y = ln 3
(x 2
− x +1 ) 2

1 3
= ln( x − 1) 2 − ln x − x + 1 ( 2
) 2

1 3
⇒ ln y =
2
ln( x − 1) − ln x 2 − x + 1
2
( )
Now diff. w.r.t x
d 1 d 3 d
dx
ln y =
2 dx
ln( x − 1) −
2 dx
ln x 2 − x + 1 ( )
1 dy 1 1 d 3 1 d 2
⇒ = ( x − 1) − x − x +1 ( )
y dx 2 x − 1 dx 2 x 2 − x + 1 dx ( )
1 3 1 3 ( 2 x − 1)
= (1) − ( 2 x − 1) = −
2 ( x − 1) 2 x2 − x + 1 ( )
2 ( x − 1) 2 x 2 − x + 1 ( )
dy  x 2 − x + 1 − 3 ( 2 x − 1)( x − 1) 
⇒ = y 
dx  2 ( x − 1) x 2 − x + 1  ( )
1
( x − 1) 2  x2 − x + 1 − 3 2x2 − x − 2x + 1 ( ) 
= ⋅
( x2 − x + 1 )
3
2  2 ( x − 1) x 2 − x + 1 ( ) 

 2 2

− + − + + − −5 x 2 + 8 x − 2
=  
x x 1 6 x 3 x 6 x 3
=
 1 3 +1  1 5

 2 ( x − 1)
1−
2 x2 − x + 1 2
(
 ) 2 ( x − 1) 2
(x 2
)
− x +1 2

dy 5x2 − 8x + 2
⇒ = − 5 Ans.
dx 2 x − 1 x2 − x + 1 ( ) 2

(xv) y =
( x + 2) ⋅ x −1
x2 + x − 2
2 2

⇒ y =
( x + 2) ⋅ x −1
⇒ y =
( x + 2) ⋅ x − 1
2
x + 2x − x − 2 x ( x + 2 ) − 1( x + 2 )

http://www.mathcity.org
FSc-II / Ex- 2.6 - 12 MathCity.org
2

⇒ y =
( x + 2) ⋅ x − 1 ⇒ y =
2−
1
⇒ y =
3
( x + 2) 2 ( x + 2) 2
( x + 2 )( x − 1)
Now diff. w.r.t x
3
dy d
= ( x + 2) 2
dx dx
Do yourself
2.1.3 Derivative of Hyperbolic Function (page 85)
The hyperbolic functions are define by
e x − e− x e x + e− x
sinh x = , x∈R ; cosh x = , x∈R
2 2
sinh x e x − e− x
and tanh x = = , x∈R
cosh x e x + e − x
The reciprocal of these functions are defined as;
1 2 1 2
csch x = = x − x , x ∈ R − {0} ; sech x = = x , x∈R
sinh x e − e cosh x e + e− x
1 e x + e− x
and coth x = = , x ∈ R − {0}
tanh x e x − e − x
and there derivatives are
d d
(i) ( sinh x ) = cosh x (ii) ( cosh x ) = sinh x
dx dx
d d
(iii) ( tanh x ) = sech 2 x (iv) ( coth x ) = − csch 2 x
dx dx
d d
(v) ( sech x ) = − sech x tanh x (vi) ( csch x ) = − csch x coth x
dx dx
Proof:
d d  e x − e− x  d  1 x − x  1 d x − x
(i) ( sinh x ) =   =  (e − e )  = (e − e )
dx dx  2  dx  2  2 dx
1 d d  1 1
=  e x − e − x  = ( e x − e − x ( −1) ) = ( e x + e− x )
2  dx dx  2 2
 e x + e− x 
=  = cosh x
 2 
(ii) Similar as above.
(iii) See the below (iv) proof.
d d  e x + e− x 
(iv) coth x =  x − x 
dx dx  e − e 

http://www.mathcity.org
MathCity.org FSc-II / Ex- 2.6 - 13

d x d
(e x
− e− x )
dx
( e + e− x ) − ( e x + e − x ) ( e x − e− x )
dx
= 2
( e x − e− x )
=
(e x
− e − x )( e x + e − x (−1) ) − ( e x + e − x )( e x − e − x (−1) )
2
(e x
− e− x )

=
(e x
− e − x )( e x − e − x ) − ( e x + e− x )( e x + e− x )
2
(e x
− e− x )
2 2

=
(e x
− e− x ) − ( e x + e− x )
2
(e x
− e− x )
(e2 x + e −2 x − 2e x e− x ) − (e2 x + e−2 x + 2e x e− x )
= 2
(e x
− e− x )
e2 x + e −2 x − 2 − e2 x − e−2 x − 2
= ∵ e x e − x = e0 = 1
−x 2
(e x
−e )
2
−4  2 
= 2
= −  x − x  = − csch 2 x
(e x
− e− x ) e −e 

( sech x ) =  x − x  = 2 ( e x + e− x ) = 2 ( e x + e− x )
d d 2 d −1 d −1
(v)
dx dx  e + e  dx dx
 −1−1 d 
= 2 ( −1) ( e x + e− x ) ( e x + e− x ) 
 dx 
−2 −2
= −2 ( e x + e − x ) ( e x + e− x ( −1) ) = 2 ( e x − e− x )
( e x + e− x )
−2 ( e x − e − x ) 2 ( e x − e− x )
= x =−
( e + e− x )( e x + e− x ) ( e x + e− x ) ( e x + e− x )
= − sech x tanh x
(vi) Do yourself as above (v).
2.14 Derivative of Inverse Hyperbolic Function (page 86)
d 1 d 1
(i) sinh −1 x = (ii) cosh −1 x =
dx 1 + x2 dx x2 − 1
d 1 d 1
(iii) tanh −1 x = 2
(iv) coth −1 x =
dx 1− x dx 1 − x2

http://www.mathcity.org
FSc-II / Ex- 2.6 - 14 MathCity.org

d −1 d −1
(v) sech −1 x = (vi) csch −1 x =
dx x 1 − x2 dx x 1 + x2
Proof:
(i) Let y = sinh −1 x ⇒ sinh y = x
differentiate w.r.t. x.
d d dy dy 1
sinh y = x ⇒ cosh y = 1 ⇒ =
dx dx dx dx cosh y
dy 1
⇒ = ∵ cosh 2 x − sinh 2 x = 1
dx 2
1 + sinh y
dy 1
⇒ = ∵ sinh y = x
dx 1 + x2
(ii) Do yourself as above.
(iii) Do yourself as (iv) below or see book at page 88.
(iv) Let y = coth −1 x ⇒ coth y = x
differentiate w.r.t. x
d d dy dy 1
coth y = x ⇒ − csch 2 y = 1 ⇒ =
dx dx dx dx − csch 2 y
dy 1
⇒ = 2
∵ coth 2 y − 1 = csch 2 y
dx −(coth y − 1)
dy 1 1
⇒ = =
dx − coth y + 1 1 − coth 2 y
2

dy 1
⇒ = ∵ coth y = x
dx 1 − x 2
(v) Suppose y = sech −1 x ⇒ sech y = x
differentiate w.r.t. x
d d dy dy 1
sech y = x ⇒ − sech y tanh y = 1 ⇒ =
dx dx dx dx − sech y tanh y
dy −1
⇒ = ∵ 1 − tanh 2 y = sech 2 y
dx sech y 1 − tanh y 2

dy −1
⇒ = ∵ sech y = x
dx x 1 − x 2
(vi) Do yourself as above

http://www.mathcity.org
MathCity.org FSc-II / Ex- 2.6 - 15

Question # 3
dy
Find if
dx
π π
(i) y = cosh 2 x (ii) y = sinh 3 x (iii) y = tanh −1 (sin x), − <x<
2 2
 x
(iv) y = sinh −1 x3( ) (v) y = ( ln tanh x ) (vi) y = sinh −1  
2
Solution
(i) y = cosh 2 x
Diff. w.r.t x
dy d dy d dy
= cosh 2 x ⇒ = sinh 2 x (2 x) ⇒ = 2sinh 2 x
dx dx dx dx dx

(ii) Do yourself

(iii) y = tanh −1 (sin x) ⇒ tanh y = sin x


Diff. w.r.t x
d d
tanh y = (sin x)
dx dx
dy dy cos x
⇒ sech 2 y = cos x ⇒ =
dx dx sech 2 y
dy cos x
⇒ = 2
∵ cosh 2 θ − sinh 2 θ = 1
dx 1 − tanh y
∴ 1 − tanh 2 θ = sech 2 θ
cos x
= ∵ sin x = tanh y
1 − sin 2 x
cos x dy
= ⇒ = sec x
cos 2 x dx

(iv) ( )
y = sinh −1 x3 ⇒ sinh y = x3
d d 3 dy
⇒ sinh y = x ⇒ cosh y = 3x 2
dx dx dx
dy 3x 2
⇒ =
dx cosh y
3x 2
= ∵ cosh 2 y − sinh 2 y = 1
2
1 + sinh y

http://www.mathcity.org
FSc-II / Ex- 2.6 - 16 MathCity.org

3x 2 3x 2
= = . Answer
3 2 6
1+ x ( ) 1+ x

(v) Do yourself

 x x
(vi) y = sinh −1   ⇒ sinh y =
2 2
Now diff w.r.t x
d d x dy 1
sinh y =   ⇒ cosh y =
dx dx  2  dx 2
dy 1
⇒ =
dx 2cosh y ∵ cosh 2 y − sinh 2 y = 1
1 ∴ cosh 2 y = 1 + sinh 2 y
=
2 1 + sinh 2 y
1 1 1
= = = Answer.
2 2 2
2 1 + ( x / 2) 2 (4 + x ) / 2 4+ x

Error Analyst
Muzammil Ahsan 2009-11 Govt. Post Graduate Collage Jauharabad Distt. Khushab
Muhammad Usman Saleem 2013-14 DPS & IC Jauharabad
Asma Mussarat Fazaia Degree College Risalpur
Irfan Mehmood Fazaia Degree College Risalpur
Please report us error at www.mathcity.org/error

Book: Exercise 2.4


Calculus and Analytic Geometry Mathematic 12
Punjab Textbook Board, Lahore.

Available online at http://www.MathCity.org in PDF Format


(Picture format to view online).
Updated: September,12,2017.

These resources are shared under the licence Attribution-


NonCommercial-NoDerivatives 4.0 International
https://creativecommons.org/licenses/by-nc-nd/4.0/
Under this licence if you remix, transform, or build upon the
material, you may not distribute the modified material.

http://www.mathcity.org